2019
DOI: 10.1111/pin.12879
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous lung adenocarcinoma, particularly referring to EGFR‐mutated mucinous adenocarcinoma

Abstract: EGFR-mutated adenocarcinoma. Among 1159 surgically resected invasive adenocarcinomas, 189 mucinous adenocarcinomas (16%) were identified. Among these, 20%, 34% and 9.5% were EGFR mutated, KRAS mutated and ALK rearranged, respectively. Compared with EGFR-mutated nonmucinous adenocarcinoma, EGFR-mutated mucinous adenocarcinoma had no female predominance, lower grades of histological differentiation and lower TTF-1 and higher HNF-4a expressions. Moreover, for the first time, we indicated that mucin production was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…These mucin core proteins are also expressed in nonmucinous lung adenocarcinoma as well as in IMA, and their expression patterns are diverse. 16,17 Nonterminal respiratory unit (TRU)-type adenocarcinoma, which may originate from bronchial surface epithelial and glandular cells, 18 correlates with the expression of MUC5AC and MUC5B. 19,20 It indicates that the precursor cells may influence the expression patterns of secretory mucins in lung neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…These mucin core proteins are also expressed in nonmucinous lung adenocarcinoma as well as in IMA, and their expression patterns are diverse. 16,17 Nonterminal respiratory unit (TRU)-type adenocarcinoma, which may originate from bronchial surface epithelial and glandular cells, 18 correlates with the expression of MUC5AC and MUC5B. 19,20 It indicates that the precursor cells may influence the expression patterns of secretory mucins in lung neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did observe an improved PFS from 1st line targeted therapies among our current patients, these treatments were not found to be associated with the IMA prognosis in our multivariate analysis. The distinct characteristics of EGFR mutations that have been found to have no female predominance and operate in a different tumorigenic pathway in IMA could have impacted on these targeted treatment responses [ 42 ]. Finally, PD L-1 expression was not examined in all the patients in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Parenthetically, KRAS is the most common mutated gene in MACs, as well as GNAS and EGFR mutations in the latter neoplasm. [36][37][38][39] One can argue as to the nature of the MCC and its relationship to MAC, but several studies have reported an association between CPAM type 1 and MAC with KRAS. [40][41][42] Because the clinical outcome is so favorable in the cases of putative MAC in CPAM type 1, Nelson et al 43 have questioned whether these lesions only "mimic adult MAC.…”
Section: Cpam and Distinct Mutationsmentioning
confidence: 99%